Management - Dyck, Bruno; Neubert, Mitchell J. (Andover, Mass. : Cengage Learning Asia Pte Ltd, 2012)
Our textbook is unique because it presents, in each chapter, two parallel approaches to management, with a focus on helping readers think about management is linked with important issues that they will be facing in their careers.
Management basics -- The Environment and context of management -- Planning -- Organizing -- Controlling -- Leading
Includes index.
Keywords: MANAGEMENT